Experimental Investigation on the Deviated Sediment and Flow to Sediment Bypass Tunnels (SBTs) Using Submerged Plates - pejman Aminian; Ahmad Ahmadi; Samad Emamgholizadeh (Journal of Hydraulic Structures, 2019)
Sediment Bypass Tunnels (SBTs) are deviant channels that convey the current containing sediments from the upstream of the reservoir to the downstream of the dam. In this research, by applying submerged plates on the entrance of a 90-degree diversion channel for sediment transport, the effect of hydraulic parameters of flow and changes in the angle of plates on sediment transport and deviated flow are studied and compared with the state without using submerged plates. The experiments were conducted on a 10-meter-long Laboratory Flume, with a main channel of 60 cm width and a secondary channel of 30 cm width and a height of 75 cm. In this regard, the variables of Froude number and flow depth in three angles of 30, 45 and 60 degrees were considered. The results of this study highlight that an increase in Froude number on average would result in reduction of 22.2% of the channel deviated flow and reduction of 53.3% of the deviated sediment to the secondary channel. The 60-degree angle of the plates is effective in decreasing the deviated flow while the 30-degree angle is responsible for the increased deviated sediments. With a decrease in Froude number and depth along with submerged plates with a 30 degree angle, the optimum condition in conveying sediments is achieved where the maximum amount of sediments are conveyed in the minimum flow rate. Based on prediction results, the best equation to calculate the deviated sedimentation flow using the Genetic Algorithm (GA) is suggested.